Governance of Swedish school mathematics — where and how did it happen? A study of different modes of governance in Swedish school mathematics, 1910-1980 - Johan Prytz (Espacio, Tiempo y Educación, 2017)
The aim of this paper is to revise a standard narrative about governance of the Swedish school system in the period of 1910-1908. According to this narrative, the Swedish school system was centralized during this period. However, this narrative does not fit the history of Swedish mathematics education (years 1-9). The research questions are: where in the school system was change initiated and how was change enforced? On the basis of studies of syllabi, textbooks, teaching literature, teacher journals and reports from investigations and development projects, different modes of governance of school mathematics are identified. The main results are that textbook producers rather than national syllabi and exams were drivers of change in the period 1910-1960. Moreover, the centralized attempts to change school mathematics, prepared in the 1960s, were soon abandoned in the early 1970s. Thus, centralized governance of Swedish school mathematics, with the ambition to achieve change, was something that took effect relatively late and during a very short period of time.